2018
DOI: 10.1155/2018/9438046
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Length of Stay in the Intensive Care Unit: Our Clinical Experience

Abstract: Background and Aim Long hospital days in intensive care unit (ICU) due to life-threatening diseases are increasing in the world. The primary goal in ICU is to decrease length of stay in order to improve the quality of medical care and reduce cost. The aim of our study is to identify and categorize the factors associated with prolonged stays in ICU. Materials and Method We retrospectively analyzed 3925 patients. We obtained the patients' demographic, clinical, diagnostic, and physiologic variables; mortality; l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 12 publications
2
17
0
1
Order By: Relevance
“…A study of patients admitted to ICU in Turkey showed that patients with cardiovascular system diseases, multiple diseases, nervous system diseases, and cerebrovascular diseases had a prolonged stay in the ICU. 14 A study conducted on the characteristics of the elderly admitted in medical ICU in Morocco, the mean ICU length of stay was 6.6 ± 6 days for all admissions, and the figures for survivors and nonsurvivors were similar. The mean age of the patients in this study was 70 years as in our study, and it considered only medical ICU patients and 64% of deaths occurred during the first five days after admission in ICU 6 .…”
Section: Discussionmentioning
confidence: 97%
“…A study of patients admitted to ICU in Turkey showed that patients with cardiovascular system diseases, multiple diseases, nervous system diseases, and cerebrovascular diseases had a prolonged stay in the ICU. 14 A study conducted on the characteristics of the elderly admitted in medical ICU in Morocco, the mean ICU length of stay was 6.6 ± 6 days for all admissions, and the figures for survivors and nonsurvivors were similar. The mean age of the patients in this study was 70 years as in our study, and it considered only medical ICU patients and 64% of deaths occurred during the first five days after admission in ICU 6 .…”
Section: Discussionmentioning
confidence: 97%
“…Toptas et al showed that length of stay of in the ICU is significantly longer for non-surgical patients than for surgical patients (P < 0.01). 24 Therefore, it is difficult to compare the length of stay of the present study cohort with other studies dealing with geriatric ICU patients. Most of them include predominantly medical patients, mainly without restrictions regarding the reason for admission.…”
Section: Discussionmentioning
confidence: 93%
“…However, the accuracy of ICU LOS predictions made by clinicians has been poorly evaluated. Studies reported that variables, such as post-operative monitoring, systolic arterial pressure, creatinine level, invasive mechanical ventilation, and active infection et al, were associated with ICU LOS [47][48][49][50]. In the ICU time-length study, Huang performed two types of analyses, in which a singlefactor correlation analysis found a large number of changes in the blood cell indexes of hospitalized patients in relation to their in-hospital mortality, both mentioning the ratio of monocytes to basophils; in the multifactorial regression, basophils, leukocytes, MCHC were independent factors associated with in-hospital mortality [51].…”
Section: Discussionmentioning
confidence: 99%